Diallel analysis and genetic differentiation of tropical and temperate maize inbred lines - Kulka,Vania Portes (2018)
Abstract This study aimed to evaluate hybrids obtained by the cross among temperate × tropical elite maize lines, and to determine the genetic diversity and population differentiation of these inbred lines. Forty-nine hybrids were evaluated for seed yield, plant and ear heights, and for severity of Phaeosphaeria maydis and Exserohilum turcicum in four environments in Brazil. Hybrids were obtained from a partial diallel that involved seven tropical and seven temperate lines. Twenty-two SSR primers were used to evaluate the genetic relationship among the lines. Diallel showed the existence of significance for GCA and SCA effects; the genetic control of the traits was associated with additive and non-additive genetic effect. Results showed that exotic and previously protected temperate maize germplasm may provide novel alleles for resistance to P. maydis and E. turcicum and increase yield in tropical maize. Tropical inbred lines were allocated in different heterotic groups, suggesting an admixture condition among temperate and tropical materials.